The Role of Behavioral Factors in the Implementation of Environmental, Social, and Governance (ESG) - Farah Rialista; Fitra Dharma; Liza Alvia (ROE: Research of Economics and Business, 2026)
Globally, Environmental, Social, and Governance (ESG) practices have become a strategic pillar for corporations. However, behind formally announced commitments, a substantial gap often remains between promises and actual practices a gap that frequently leads to greenwashing and weakens accountability. This literature review examines the non-technical factors underlying successful ESG adoption, with particular emphasis on the central role of human dynamics in decision-making processes, incentive design, reporting practices, and organizational cultural transformation. Through a critical analysis of twenty recent empirical and theoretical studies, this article demonstrates that ESG success depends not only on reporting standards or regulatory pressure but also on underlying assumptions about human motivation, cognitive bias, risk perception, and accountability systems that emphasize clarity, simplicity, and stakeholder accessibility. The findings indicate that firms tend to respond to ESG ratings symbolically unless incentives are strategically aligned, leadership is genuinely committed, and accounting systems recognize the intrinsic value of environmental and social dimensions rather than treating them merely as instrumental tools.